(untitled) - Khoo, Iam-Choon (New Jersey, 2007)
An excellent professional reference and superior upper-level student text, Liquid Crystals, Second Edition is a comprehensive treatment of all the basic principles underlying the unique physical and optical properties of liquid crystals. Written by an internationally known pioneer in the nonlinear optics of liquid crystals, the book also provides a unique, in-depth discussion of the mechanisms and theoretical principles behind all major nonlinear optical phenomena occurring in liquid crystals
Keywords: Liquid crystals,Tinh thể lỏng